Table of Content - - (Journal of engineering sciences and information technology, 2024)
Table of Content: 1. Al-Sulaymaniyah Tekkia as a station for Shami Pilgrimage during Ottoman Era (1516 AD-1918 AD) Eng. Amani Khalil Al-Rahhal 2. The Blockchain Technology Applications and its Impact on Governance Performance: A Field Study on the Transportation Sector in Palestine Dr. Maher Fuad Abu Farhah 3. Evaluating the Impact of Artificial Intelligence in Managing Construction Engineering Projects Mr. Abdullah Mohammad Abdelhamid Alhasan, Eng. Ebrahim Khaled Ebrahim Alawadhi 4. Enhancing Object Detection Techniques Through Transfer Learning and Pre-trained Models Asst-Lecturer Ashwaq Katham Mtashre, Asst-Lecturer Dhakaa Mohsin Kareem, Asst-Lecturer Zainab Abd Al-Abbas Muhsen 5. Network Classifier on Iris data Using MATLAB Asst-Lecturer Jenan Jader Msaad, Lecturer Ruwaidah F.Albadri, Asst-Lecturer Alaa Majeed Shnin